The emergence of the customer relationship portfolio of a new venture: a networking process. Issue 5 (8th January 2019) - La Rocca, Antonella; Perna, Andrea; Sabatini, Andrea; Baraldi, Enrico
Abstract : Purpose: While several studies have focused on the initial phases of new ventures and their first customer and supplier relationships, we have a limited understanding of how the new venture's portfolio of customer relationships emerges. This paper aims to explore the emergence of the customer relationship portfolio of a new venture and to investigate the effects of early relationships on subsequent ones. Design/methodology/approach: Methodologically, the authors rely on a longitudinal single case study of a new venture which develops, implements and sells customized cost-management software. The study is exploratory and based on 24 in-depth interviews. Findings: The findings show that the development of a customer portfolio depends on the cumulative effect of heterogeneous elements and network connections. These include the initial link between the new venture and the first customer and a subsequent series of interconnections that develop with the emerging network capability of the new venture. Originality/value: As one of the few studies that explore the emergence of new ventures' customer relationship portfolio, this study demonstrates the value of applying a relational/network approach for studying relationship portfolio dynamics.